Pemerolehan bahasa kanak-kanak Melayu berasaskan teori pemerolehan bahasa oleh Steinberg (1995) (Jurnal Bahasa, 2005)
The aim of this research is to identify language acquisition among Malay children based on the language acquisition theory suggested by Steinberg (1995). Studies and observations were made on 40 Malay children which consist offour levels of language acquisition. This study was carried out at the MARDI Kindergarten, Serdang, and Kinder-garten Perpaduan Taman Sri Serdang, Selangor. This study was based on the observation approach on the aspects of acquisition and excel-lence in mastering language among children. Picture based aids were used in activities to arouse them to speak. This study focuses on the qualitative and quantitative approach. The results of this study sup-ported Steinberg's discovery (1995) that the excellence in language acquisition among children depends on the age level.